2015
DOI: 10.1186/s12890-015-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepacia complex: clinical course in cystic fibrosis patients

Abstract: BackgroundPulmonary deterioration after B.cepacia complex (BCC) colonization has a heterogeneous pattern. The aim was to investigate the clinical outcome of BCC colonization in CF patients chronically colonized with P. aeruginosa.MethodsCF patients chronically colonized with P. aeruginosa were divided into three groups: intermittent (I), chronic (II) and no colonization (III) with BCC. Body mass index (BMI) percentile and spirometric parameters were analyzed at three different times in each group.ResultsFifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
6
38
0
1
Order By: Relevance
“…Opportunistic pathogens capable of causing infections in vulnerable individuals were also found such as the Burkholderia cepacia complex (BCC), Pseudomonas aeruginosa , Stenotrophomonas maltophilia , Acinetobacter baumannii , Ralstonia pickettii , Pseudomonas fluorescens and Sphingomonas paucimobilis [4248]. BCC strains can infect and cause lung decline in patients with cystic fibrosis [49]. These bacteria could potentially act as a reservoir for the spread of antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Opportunistic pathogens capable of causing infections in vulnerable individuals were also found such as the Burkholderia cepacia complex (BCC), Pseudomonas aeruginosa , Stenotrophomonas maltophilia , Acinetobacter baumannii , Ralstonia pickettii , Pseudomonas fluorescens and Sphingomonas paucimobilis [4248]. BCC strains can infect and cause lung decline in patients with cystic fibrosis [49]. These bacteria could potentially act as a reservoir for the spread of antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Mean rate of FEV 1 % predicted decline in CF patients chronically colonized with Bcc was significantly higher than expected in all ages [6], although there was no correlation to Bcc species. In our report, chronic Bcc colonization and clinical stability had been present over a long period.…”
Section: Discussionmentioning
confidence: 97%
“…P. aeruginosa is considered the main bacterium that affects people with CF, causing chronic lung infections, which leads to high rates of morbidity and mortality, and once the bacteria is established, it is difficult to eradicate it (Winstanley et al, 2016). On the other hand, patients colonized in a chronic manner with B. cepacia present a worse prognosis of the disease, as the use of antibiotics becomes more frequent they also have a greater deterioration of lung function and the rate of mortality is higher compared to that patients colonized by only P. aeruginosa (Gilligan, 2014; Folescu et al, 2015). It has been reported that B. cepacia and P. aeruginosa can form mixed biofilms in the lungs of people with CF, since, P. aeruginosa through its extracellular products can increase the attachment of B. cepacia by modifying the lung epithelial cells on its surface; however, the same does not occur in patients previously colonized with B. cepacia (Saiman et al, 1990).…”
Section: Nets Formation By Microorganisms Of Cystic Fibrosismentioning
confidence: 99%
“…It has been reported that B. cepacia and P. aeruginosa can form mixed biofilms in the lungs of people with CF, since, P. aeruginosa through its extracellular products can increase the attachment of B. cepacia by modifying the lung epithelial cells on its surface; however, the same does not occur in patients previously colonized with B. cepacia (Saiman et al, 1990). Coinfection between the two bacteria results in a rapid decline in lung function and a high mortality rate (Folescu et al, 2015). In CF the simple colonization by S. aureus is generally considered of better prognosis than those colonized with P. aeruginosa ; but in some cases, the presence of small-colony variants (SCV) of S. aureus is associated with the most advanced lung disease in CF, and the phenotype of this bacterium in a coinfection with P. aeruginosa causes disease worsening (Besier et al, 2007; Hubert et al, 2013).…”
Section: Nets Formation By Microorganisms Of Cystic Fibrosismentioning
confidence: 99%